Indirect procurement outsourcing issues and opportunities in context of Bangladesh based firms - Arefeen, Mohammad Shahe (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.